The Regulatory Effects of Exercise and Metformin on Biomarkers in Obesity: A Focus on Uric Acid, Irisin, Adiponutrin, Adropin, and Copeptin - Akbulut, Taner; Cinar, Vedat; Avcu, Emsal Cagla; Yasul, Yavuz; Aydemir, Isa; Kuloglu, Tuncay; Aydin, Suleyman (Mdpi, 2025)
Background and Objectives: Obesity has become one of the most significant health problems nowadays, with its prevalence rapidly increasing. Approaches such as diet and exercise play an important role in the treatment of obesity. This study aimed to investigate the responses of uric acid, irisin, adiponutrin, adropin, and copeptin levels to exercise and metformin intervention in obesity. Materials and Methods: Thirty-six male Sprague-Dawley rats were randomly divided into seven groups: healthy control (HC), sham (S), obese control (OC), metformin (M), exercise (E), metformin + exercise (ME), and decapitation (D). After obesity was induced through a 12-week high-fat diet, obese rats underwent a 4-week aerobic exercise and metformin intervention. Results: Uric acid, irisin, adiponutrin, adropin, and copeptin levels were determined using an ELISA method. Copeptin levels significantly decreased in the ME group (p < 0.001). Irisin levels significantly increased in the E and ME groups (p < 0.001). The most notable increases in adropin levels occurred in the E and ME groups (p < 0.001). Uric acid levels were highest in the OC group but significantly lower in the E and M groups (p < 0.001). Adiponutrin levels did not change in response to exercise or metformin intervention in obesity (p > 0.05). Conclusions: These findings suggest that exercise and metformin intervention may play an effective role in obesity management.
Keywords: exercise; metformin; obesity; adipokines; myokines